(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Economic and financial sector reforms have placed higher disposable incomes with the public. Availability of a variety of new financial products on both, credit and investment sides, which are provided by a host of financial intermediaries has necessitated that the investing public understands the degree of each product and product supplier, and takes an informed decision about where s(he) should invest. At the same time, those who are not part of the formal financial system need to be educated about banking and why they should have a relationship with banks. Financial literacy is considered an important element for promoting financial inclusion and ultimately financial stability. Financial literacy would benefit the financially-excluded by enabling them to understand the benefits and the ways to join the formal financial system. It could also benefit the financially included by helping them make informed choices about the products and services available in the market to their best advantage.The financial market has been significantly changing after liberalization and has been putting forth a few open doors for speculator as well as for the corporate. Today financial services are becoming more open, financial market offers bunch of items with mind boggling highlights and services, leaving numerous people poorly outfitted to cope up with the complex financial needs. The economies around the globe have progressively considered financial literacy as a key column for the development of their financial framework. The financial education has grown a considerable measure from its pre liberalization starting to the present day conditions of post liberalization corporate period. The present investigation takes into accounts the distinctive measurements of financial literacy and education in India i.e. financial education its importance, determinants and, part of administrative experts in India. The investigation concludes that the procedure for enhancing financial prosperity of people in India ought to center the youthful investors.